Antibacterial activities for root extracts of (goldenrods) Solidago canadensis L treated by Nano and bio fertilizer - Sareea Al-Rekaby, Layth; ALhatemi, khalid Mohsein Atiyah (Al-Qadisiyah Journal of Pure Science, 2020)
This experiment was done to find out to assess the effect of three concentration of Nano fertilizer 0, 1 and 2 gm./L , and the bio fertilizer at two levels 0 and 20 gm./L and their interactions on production of active ingredient of Solidago canadensis L. (goldenrods) , that planted in plastic pots. the active compounds in roots were measured After finishing experiment by Gas Chromatography-Mass Spectrometry (GC-MS) ( Manufacturer: Agilent 5977 A MSD , USA) The show results that the experimental treatment effect a significant increase in all measured parameters. Chemical description of extract has been carried out using gas chromatography and mass spectrometry (GC-MS). forty identified components in S. canadensis of total compounds in the fundamental compounds were identified as medical activity. The efficacy test included the effect of the alcohol extracts of the plant by inhibiting the growth of bacterial genera by the method of diffusion by drilling on the Mueller-Hunton medium. The laboratory experiment was carried out using Complete Randomized Design (CRD) with two factors (6 × 2) and three replicates for each treatment, the first factor, the type of extract for each plant treatment, and the second, the concentrations of the extract (100 and 200 mg / ml). The averages were compared when the differences were Significance using modified significance test RLSD with a significance level of 0.01. The results show : The higher level increased of concentration Benzofuran after treatment by 2 gm./L Nano fertilizer without Bio fertilizer, The higher level increased of concentration Stigmasta-7,16-dien-3-ol, (3.beta).after treatment by treatment 1 gm./L Nano fertilizer and 20 gm. /L Bio fertilizer , The higher level increased of concentration Phthalic acid after treatment by treatment 1 gm./L Nano fertilizer and 20 gm. /L Bio fertilizer , The higher inhibition diameter of Staphylococcus aureus after treatment by treatment 1 gm./L Nano fertilizer and 20 gm. /L Bio fertilizer , Which is Achieve 15.00 mm and The higher inhibition diameter of Pseudomonas aeruginosa after treatment by treatment 2 gm./L Nano fertilizer and 20 gm. /L Bio fertilizer , Which is Achieve 15.00 mm. Key wards : goldenrods , Solidago Canadensis , Bioactive constituents, Antibacterial activities, Root extracts, GC-MS , nanofertilizer and biofertilizer